Socialna varnost samozaposlenih - Bagari, Sara (Delavci in delodajalci, 2025)
The contribution analyses the key challenges of ensuring social security for the self-employed in the context of structural changes in the contemporary labour market, where the growth of non-standard forms of work and the increasing heterogeneity of the self-employed significantly affect the effectiveness of existing social protection mechanisms. The importance of proper classification of contractual relationships is emphasised, as misclassification of status may lead to exclusion from, or insufficient coverage within, the social security system. The analysis encompasses both a broader perspective and the specific features of the Slovenian legal framework, which, despite the formal mandatory inclusion of the self-employed in social insurance schemes, continues to reveal significant gaps in their effective access to social security and the rights arising from it. The contribution concludes that comprehensive and mandatory inclusion of the self-employed in a unified social security system represents the most appropriate approach, but only insofar as it simultaneously takes into account the specific characteristics of self-employment.
Keywords: dejanski dostop; dependent self-employed; effective access; formal access; formalni dostop; nestandardni samozaposleni; non-standard self-employed; odvisni samozaposleni; samozaposleni; samozaposlitev; self-employed; selfemployment; social insurance; social security; socialna varnost; socialno zavarovanje